THE Effect of Interactive E-Booklets on Students Digital Literacy - Fitriati, Resti; Ikbal; Mikyal Hardiyati (Jurnal Profesi Keguruan, 2025)
The aim of this scientific article research is to develop digital-based learning media in the form of an interactive e-booklet on the diversity of fish species and to determine the effect of using e-booklet learning media on the digital literacy of students at SMA Al Fattah Terboyo Semarang. This type of research is Research and Development (RnD). The author used a quasi-experimental method with a one-group pretest-posttest design to identify the effect of treatment involving one group of subjects, namely the tenth-grade students of SMA Al Fattah Terboyo Semarang. Data were collected through digital literacy tests related to biology material and linked to digital literacy. The results of the study indicate that the use of e-booklets as learning media has a positive effect on improving students' digital literacy, as seen from the average pretest and posttest scores of the students, which increased from 65.83 to 81.50. This research suggests that further research can redevelop e-booklets into other interactive media to increase user involvement.